THE INFLUENCE OF ASSET EFFICIENCY, FINANCIAL PERFORMANCE, AND FINANCIAL LEVERAGE ON SUSTAINABLE GROWTH RATE THROUGH GOOD CORPORATE GOVERNANCE - Rosiati Parapat; Endang Ruhiyat; Sugiyanto (ZILLZELL MEDIA PRIMA, 2024)
This study aims to examine the Effect of Asset Efficiency, Financial Performance and Financial Leverage on Sustainable Growth Rate Through Good Corporate Governance. This study is classified as an associative quantitative study. The type of data used is secondary data obtained from www.idx.co.id and the company's website. The population in this study is the Manufacturing Companies in the Consumer Goods Industry Sector listed on the IDX for the 2018-2022 Period. While the sample of this study was determined by the sampling technique used in this study is non-probability sampling, namely purposive sampling so that 20 sample companies were obtained that met the criteria. The analysis method used is Panel Data Model Regression analysis. The results of this study indicate that asset efficiency does not affect the Sustainable Growth Rate (1), financial performance does not affect the Sustainable Growth Rate (2), financial leverage affects the Sustainable Growth Rate (3), asset efficiency affects Good Corporate Governance (4), financial performance affects Good Corporate Governance (5), financial leverage affects Good Corporate Governance (6). Sustainable Growth Rate has an effect on Good Corporate Governance (7), Asset Efficiency does not have a significant effect on the Sustainable Growth Rate variable through the Good Corporate Governance variable (8), Financial Performance does not have a significant effect on the Sustainable Growth Rate variable through the Good Corporate Governance variable (9), Financial Performance does not have a significant effect on the Sustainable Growth Rate variable through the Good Corporate Governance variable (10). Leverage does not have a significant effect on the Sustainable Growth Rate variable through the Good Corporate Governance variable (10).